2018
DOI: 10.4186/ej.2018.22.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of Abiotic Sulfide Oxidation in Microbial Fuel Cells Treating High-Sulfate Wastewater

Abstract: Microbial fuel cells (MFCs) have been considered as an alternative for the treatment and energy recovery of organic wastewater containing sulfate, which cannot be achieved via conventional anaerobic treatment processes. This study investigates the performances and mechanisms of two-compartment single-chamber MFCs treating sulfaterich organic wastewater at the chemical oxygen demand (COD) to sulfate ratio of 1, 3, and 6 in MFC1, MFC3, and MFC6, respectively. The first compartments functioned as anaerobic biorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In addition, the higher abundance of MG and SRB in M2H indicated that organic removal in M2H was mainly associated with methanogenesis and sulfate reduction. An increase in OLR with a high COD-to-sulfate ratio promoted the growth of MG and SRB, resulting in low electricity generation [ 46 ]. The increase in MG such as Methanosarcina (OTU00302) and Methanobacterium (OTU00346), which can utilize acetate and H 2 as substrates, enhanced the utilization of organic substances in PWW for methane production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the higher abundance of MG and SRB in M2H indicated that organic removal in M2H was mainly associated with methanogenesis and sulfate reduction. An increase in OLR with a high COD-to-sulfate ratio promoted the growth of MG and SRB, resulting in low electricity generation [ 46 ]. The increase in MG such as Methanosarcina (OTU00302) and Methanobacterium (OTU00346), which can utilize acetate and H 2 as substrates, enhanced the utilization of organic substances in PWW for methane production.…”
Section: Resultsmentioning
confidence: 99%
“…In the OCS and AS, Nitrospirota (Thermodesulfovibrionia) was the most abundant group, this bacterial group is characterized by anaerobic sulfate reducing metabolism [90,91]. Dyella, Smithella, Desulfusarcinaceae, Aminicenantales were bacteria enriched in AB and AS with members of electroactive bacteria found in MFC, some of them are also sulfate reducers [92][93][94].…”
Section: Analysis Of the Composition Of The Microbial Communities (In...mentioning
confidence: 99%